A fatal case of spinal tuberculosis mistaken for metastatic lung cancer: recalling ancient Pott's disease - Duchna Hans-Werner; Weber Andreas; Nicolas Volkmar; Tannapfel Andrea; Ringshausen Felix C; Schultze-Werninghaus Gerhard; Rohde Gernot (BMC, 2009)
Abstract Background Tuberculous spondylitis (Pott's disease) is an ancient human disease. Because it is rare in high-income, tuberculosis (TB) low incidence countries, misdiagnoses occur as sufficient clinical experience is lacking. Case presentation We describe a fatal case of a patient with spinal TB, who was mistakenly irradiated for suspected metastatic lung cancer of the spine in the presence of a solitary pulmonary nodule of the left upper lobe. Subsequently, the patient progressed to central nervous system TB, and finally, disseminated TB before the accurate diagnosis was established. Isolation and antimycobacterial chemotherapy were initiated after an in-hospital course of approximately three months including numerous health care related contacts and procedures. Conclusion The rapid diagnosis of spinal TB demands a high index of suspicion and expertise regarding the appropriate diagnostic procedures. Due to the devastating consequences of a missed diagnosis, Mycobacterium tuberculosis should be considered early in every case of spondylitis, intraspinal or paravertebral abscess. The presence of certain alarm signals like a prolonged history of progressive back pain, constitutional symptoms or pulmonary nodules on a chest radiograph, particularly in the upper lobes, may guide the clinical suspicion.